1960
DOI: 10.1039/tf9605600357
|View full text |Cite
|
Sign up to set email alerts
|

The palladium + hydrogen equilibrium at high pressures and temperatures

Abstract: Isotherms of the palladiumfhydrogen system have been determined up to 990 atm at supercritical temperatures from 326" to 477°C. At the highest pressures the atomic ratio H/Pd in the solid phase exceeds 0.59, assumed as a limiting value in Lacher's theory although the theoretical equation reproduces the general features of the isotherms, which show the persistence of H+H interaction above the critical region. The new isotherms are correlated with existing measurements for the critical region and for the same pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

1962
1962
2013
2013

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(28 citation statements)
references
References 0 publications
0
28
0
Order By: Relevance
“…Levine and Weale [17] found that the heat of absorption increases (becomes less exothermic) with increasing hydrogen to palladium ratio at higher pressures and at temperatures above the critical point (Table 4). According to Levine and Weale [17] the relationship between enthalpy of absorption and composition is linear, with a change in gradient at approximately 0.5, they attribute this behavior to lattice expansion.…”
Section: Heat Of Formation Of Palladium Hydridementioning
confidence: 97%
See 4 more Smart Citations
“…Levine and Weale [17] found that the heat of absorption increases (becomes less exothermic) with increasing hydrogen to palladium ratio at higher pressures and at temperatures above the critical point (Table 4). According to Levine and Weale [17] the relationship between enthalpy of absorption and composition is linear, with a change in gradient at approximately 0.5, they attribute this behavior to lattice expansion.…”
Section: Heat Of Formation Of Palladium Hydridementioning
confidence: 97%
“…Thus some researchers [17] have found that the heat of absorption varies with composition but the data of other authors [18,26] suggest that this is not true. Let us examine the data of Levine and Weale [17] in more detail.…”
Section: Heat Of Formation Of Palladium Hydridementioning
confidence: 98%
See 3 more Smart Citations